Observations of native bumble bees inside of commercial colonies of Bombus impatiens (Hymenoptera: Apidae) and the potential for pathogen spillover. Issue 4 (7th June 2018) - Hicks, B.J.; Pilgrim, B.L.; Perry, E.; Marshall, H.D.
Abstract: Many fruit producers use commercial colonies of Bombus impatiens Cresson (Hymenoptera: Apidae) to supplement crop pollination by native bees. A small number of Newfoundland (Newfoundland and Labrador, Canada) farmers forego purchasing new colonies and, instead, purchase previously used colonies from crops in other provinces. This practice has potentially dangerous implications that may adversely affect future native bee diversity in Newfoundland. This study is the first to record the presence of native bumble bee species inside the colonies of new and pre-used commercial B. impatiens and the first to look at diseases in native bumble bees from Newfoundland. Polymerase chain reaction and taxon-specific oligonucleotides were used to screen the commercial and native bumble bee species for pathogens. Crithidia bombi (Lipa and Triggiani), Apicystis bombi (Liu, Macfarlane, and Pengelly), Nosema bombi Fantham and Porter, Nosema ceranae Fries et al., and species of Ascosphaera Olive and Spiltoir, were detected in native bumble bees that were collected from inside the new and pre-used commercial B. impatiens . Crithidia bombi, A. bombi, and N. bombi were also detected among native bees that were collected away from the commercial colonies. Nosema apis (Zander) and Melissococcus plutonius (White) were not detected in any of the bees tested. The mixing of native bumble bees in B. impatiens colonies increases the potential for pathogen spillover and spillback that may threaten the small and vulnerable island bee fauna. Résumé: De nombreux producteurs de fruits utilisent les colonies commerciales de Bombus impatiens Cresson (Hymenoptera: Apidae) pour compléter la pollinisation des cultures par les abeilles indigènes. Un petit nombre d'agriculteurs de Terre-Neuve (Terre-Neuve-et-Labrador, Canada) renoncent à l'achat de nouvelles colonies et, au lieu de cela, achètent des colonies déjà utilisées dans les cultures d'autres provinces. Cette pratique a des implications potentiellement dangereuses qui pourraient nuire à la diversité future des abeilles indigènes à Terre-Neuve. Cette étude est la première à signaler la présence d'espèces de bourdons indigènes à l'intérieur des colonies de B. impatiens commerciales nouvelles et pré-utilisées et la première à examiner les maladies chez les bourdons indigènes de Terre-Neuve. La réaction en chaîne par polymérase et les oligonucléotides spécifiques du taxon ont été utilisés pour cribler les espèces commerciales de bourdons indigènes et les agents pathogènes. Crithidia bombi (Lipa et Triggiani), Apicystis bombi (Liu, Macfarlane et Pengelly), Nosema bombi Fantham et Porter, Nosema ceranae Fries et al., et les espèces d' Ascosphaera Olive et Spiltoir, ont été détectés chez des bourdons indigènes qui ont été recueillis à l'intérieur du B. impatiens commercial nouveau et pré-utilisé. Crithidia bombi, A. bombi et N. bombi ont également été détectés parmi les abeilles indigènes qui ont été recueillies loin des colonies commerciales. Nosema apis (Zander) et Melissococcus plutonius (White) n'ont été détectés chez aucune des abeilles testées. Le mélange de bourdons indigènes dans les colonies de B. impatiens augmente le risque de débordements et de retombées pathogènes qui pourraient menacer une petite population vulnérable d'abeilles insulaires.